Experience and Emotion in Empirical Translation Research with Think-Aloud and Retrospection - Hansen, Gyde (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractIn empirical process-oriented translation research with different kinds of introspection, two important questions are raised repeatedly: 1. Does concurrent verbalization, like Think-aloud, have an influence on the translation process and 2. What do we actually learn from introspective methods like think-aloud and retrospection? Based on ideas from modern psychology and brain research, it is argued that think-aloud must have an impact on the translation process. Furthermore, it is suggested that it is not only spontaneous, unmodified thoughts about the actual task that are verbalized, but also memories, reflections, justifications, explanations, emotions and experiences.